Studi Kasus: Terapi Musik Klasik dan SP 1–4 untuk Mengelola Skizofrenia dengan Risiko Perilaku Kekerasan - Wilda Muqorona, Matsna; Muslih , Muhammad (Pustaka Galeri Mandiri, 2025)
Schizophrenia is a severe mental disorder characterized by positive symptoms such as hallucinations, delusions, and a risk of violent behavior. One non-pharmacological approach to managing this risk is the implementation of Strategy Implementation (SP 1–4), supported by classical music therapy. This study aims to describe the application of SP 1–4 combined with classical music therapy in reducing the risk of violent behavior in patients with schizophrenia. The research used a case study design with a descriptive qualitative approach. The intervention was conducted on one patient diagnosed with schizophrenia who was hospitalized in the Gili Trawangan ward at RSSA Malang, with a nursing diagnosis of risk for violent behavior. Data were collected through observation, interviews, and documentation over a four-day period. The results showed gradual improvement in the patient, including decreased emotional tension, increased relaxation, enhanced assertive communication skills, and better medication adherence. Classical music therapy also had a calming effect. The combination of SP 1–4 and classical music therapy proved effective in reducing the risk of violent behavior, helping regulate emotions, and improving compliance with treatment. Future studies should include more subjects and longer interventions to better assess long-term effects.